2015
DOI: 10.1021/acsnano.5b02611
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nanoparticles Facilitate Molecular Targeting and miRNA Delivery to Inhibit Atherosclerosis in ApoE–/– Mice

Abstract: The current study presents an effective and selective multifunctional nanoparticle used to deliver antiatherogenic therapeutics to inflamed pro-atherogenic regions without off-target changes in gene expression or particle-induced toxicities. MicroRNAs (miRNAs) regulate gene expression, playing a critical role in biology and disease including atherosclerosis. While anti-miRNA are emerging as therapeutics, numerous challenges remain due to their potential off-target effects, and therefore the development of carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
152
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 45 publications
8
152
0
Order By: Relevance
“…Importantly, quantitative polymerase chain reaction (qPCR) and immunohistochemistry analysis showed that Timp3 and Reck mRNA and protein expression were significantly decreased in partially-ligated LCA compared with contralateral RCA in non-Tg control mice (Figs. 6A, B), consistent with previous findings 34, 35, but upregulated in the LCA and aorta tissue from hIL-32α-Tg-mice LCA (Figs. 6A, B; Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…Importantly, quantitative polymerase chain reaction (qPCR) and immunohistochemistry analysis showed that Timp3 and Reck mRNA and protein expression were significantly decreased in partially-ligated LCA compared with contralateral RCA in non-Tg control mice (Figs. 6A, B), consistent with previous findings 34, 35, but upregulated in the LCA and aorta tissue from hIL-32α-Tg-mice LCA (Figs. 6A, B; Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…As such, mimics are designed as double-stranded duplexes, consisting of the guide strand identical to the miRNA and a complementary passenger strand that is often modified to increase or shift utilization to the guide strand (van Rooij, Purcell, & Levin, 2012); however, this renders the mimics difficult to transport through cell membranes and they can be degraded in circulation. To circumvent this barrier, several delivery vehicles have been put forward, including DNA vectors and adeno-associated virus (Kota, et al, 2009), lentivirus (Kortylewski & Nechaev, 2014), nanoparticles (Diaz & Vivas-Mejia, 2013; Kheirolomoom, et al, 2015), liposomes (Akinc, et al, 2010; Akinc, et al, 2008; Morrissey, et al, 2005), and stents (D. Wang, et al, 2015).…”
Section: Current Development Of Mirna Therapeutics That May Impactmentioning
confidence: 99%
“…Kheirolomoom and colleagues used the shortened version of the peptide, VHPK, to coat cationic lipoparticles (CCL) containing anti-miR-712 within its core. 33 miR-712 is a pro-atherogenic, mechanosensitive miRNA that is upregulated by distributed flow in endothelial cells. VHPK-CCLs containing miR-712 inhibitors downregulated the miR and rescued the expression of its target genes, preventing atheroma formation in Apo E −/− mice.…”
Section: Peptides For Nanoparticles In Atherosclerosismentioning
confidence: 99%